Clinical benefits of non‐taxane chemotherapies in unselected patients with symptomatic metastatic castration‐resistant prostate cancer after docetaxel: the GETUG‐P02 study. (January 2015) - Joly, Florence; Delva, Remy; Mourey, Loïc; Sevin, Emmanuel; Bompas, Emmanuelle; Vedrine, Lionel; Ravaud, Alain; Eymard, Jean‐Christophe; Tubiana‐Mathieu, Nicole; Linassier, Claude; Houede, Nadine; Guillot, Aline; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the overall benefits of non‐taxane chemotherapies in a non‐selected population including unfit patients presenting with symptoms and pain. Patients and Methods This randomized phase II study reports data from 92 patients (52% >70 years old; 40% with a performance score of 2) previously treated with taxane‐based chemotherapy, collected from 15 centres in France. Patients received i.v. mitoxantrone (MTX), oral vinorelbine, or oral etoposide, together with oral prednisone. Palliative benefit (pain response without progression of the disease), biological and tumoural responses, and toxicity profile as well as geriatric assessment (in elderly population) were analysed on an intention‐to‐treat basis. Results The palliative response rate was 17% for the whole population, and reached 29% when considering the MTX arm. Pain control was achieved in 40% of the patients. The median overall survival was 10.4 months, and was longer in palliative responders. Few grade 3–4 toxicities were observed. The subgroup analysis of elderly patients showed similar results regarding the number and dose intensity of treatments, efficacy and safety. Conclusion In a population including frail and/or elderly patients, who are poorly represented in most clinical studies, non‐taxane chemotherapy may remain a relevant option for metastatic prostate cancer having relapsed after a docetaxel‐based regimen. Although new treatment options are now approved, the decision‐making process should take into account their expected benefit/risk ratio based on the patient status.